Candida Albicans Infections: Can Homoeopathy Offer a Solution? - A Narrative Review (Advancements in Homeopathic Research, 2025)
Background: Typically, the human body has the  yeast Candida albicans, which is mostly located  in the gut, vagina, throat, and mouth. It is the most  prevalent fungal infection in humans. Seventy-five  percent of women have had vaginal candidiasis at  least once a lifetime and 5-8% of them relapse while  they are at their most fertile. Immunocompromised  individuals, denture wearers, and young children  are all susceptible to oral candidiasis. Because of  the emergence of drug resistance, new antifungal  medications are required for the effective treatment  of Candida albicans infection. Objective: The current study's objectives are to  reduce issues, encourage an early recovery, provide  specific homoeopathic treatment with symptomatic  improvement, support utilize homoeopathy in the  management and prevention of fungal maladies, and  assess the efficacy of homoeopathic medications  in suppressing Candida albicans. An overview of  the pathogenicity traits, clinical manifestations,  and participation of Candida albicans in invasive  infections is provided by the review. Method: A variety of automated database literature  searches were performed in order to gather and  condense pertinent articles. These searches included  Research Gate, PubMed and Google Scholar. Result: Homoeopathy on Candida albicans have been  shown to have possibilities for novel and dependable  techniques for inhibiting fungal infections. Interpretation: This review discusses the methods  and the remedies to inhibit Candida albicans & the  significance of homoeopathic medicine's antifungal  properties
Keywords: Antifungal; Candida albicans; Clotrimazole; Homoeopathy; In-vitro; In-vivo